Glutamic acid as coating for magnetic nanoparticles: a platform for diverse biomedical applications - Moreno, Natalia (2020)
Coating of iron oxide magnetic nanoparticles (IOMNPs) with biocompatible molecules is mandatory for biomedical applications. The election of amino acids as coating agents is because their ability in surface stabilization of IOMNPs being also inexpensive and nontoxic. In the present work, glutamic acid (GA) was selected as coating agent aiming to obtain GA-modified IOMNPs with suitable physicochemical properties, including stability, for biomedical applications. The co-precipitation method was applied to obtain IOMNPs functionalized with GA. Two experimental procedures were evaluated varying the order of GA incorporation. In the first procedure (1), an aqueous solution of GA was added under magnetic stirring to a mixture of FeCl3.6H2O and FeSO4. In the second case (2), the mixture of iron salts was added to the aqueous solution of GA. Both reactions were conducted under N2 atmosphere at 70 °C. A solution of NaOH was added dropwise. After 30 min, the supernatants were removed, and the resultant solids were washed and dried at 45 °C. The same procedure was applied to obtain bare IOMNPs. The resultant formulations were studied by FTIR, DLS to determine hydrodynamic diameter and isoelectric point, TEM, atomic absorption spectroscopy (for iron content determination) and DRX. Data analysis revealed that the method 2 allowed the efficient functionalization of IOMNPs with GA rendering a formulation with hydrodynamic diameter of 226.0 nm with spherical shape. The first method renders IOMNPs with similar properties than bare IOMNPs, revealing that functionalization with GA was not successful. The method applied to functionalize IOMNPs with GA was dependent on the order of reactants aggregation. It was possible to obtain IOMNPs coated with GA (IOMNPs@GA) with suitable properties for biomedical applications. The exposure of functional groups such as carboxylate moieties allows to the potential anchoring of diverse molecules (drugs or biomolecules) for the located treatment of multiple diseases.